(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The research aimed to test and know the role that digital leadership plays in individual work performance within the framework of the interactive role of knowledge sharing behavior, as the research problem centers on scientists’ belief that the COVID-19 virus may be with us for decades or more, and data and information were collected about the selected sample through the questionnaire. Which is considered a main tool in this research, as the sample included members of the teaching staff in a number of universities and private colleges in the Middle Euphrates region, amounting to (312) individuals. In order to support the relationship between these variables from a theoretical perspective, the study relied on measuring the digital leadership variable on a scale that includes: Five dimensions (visionary leadership, learning culture in the digital age, excellence in professional practice, systemic improvement, and digital citizenship), and as for the knowledge sharing behavior variable, a scale was adopted that includes four dimensions (written contributions, organizational communications, personal interactions, and communities of practice) While the study adopted a scale that includes four dimensions to measure individual work performance (task performance, contextual performance, adaptive performance, and adverse work behavior), the descriptive analytical approach was adopted in presenting and interpreting the information for the research, and for the purpose of analyzing and processing the data statistically, a group of Descriptive statistical measures, Pearson correlation coefficient, structural equation modeling, and modified analysis. These methods were used through the statistical program (Spss.25, Amos.25). The most prominent conclusions are that the knowledge sharing behavior in some universities and private colleges, the study sample, is The field aspect would enhance the impact of digital leadership on individual work performance, and this means the presence of knowledge sharing behavior in the field alongside digital leadership that would contribute to individual work performance in these private universities.